1985
DOI: 10.1128/mcb.5.9.2231
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphorylation in a tetradecanoyl phorbol acetate-nonproliferative variant of 3T3 cells.

Abstract: The 3T3-TNR9 cell line is a variant of Swiss 3T3 cells which does not respond mitogenically to tumor promoters, but does respond mitogenically to epidermal growth factor, fibroblast growth factor, and serum. To elucidate differences between tumor promoters and polypeptide mitogens in the pathway(s) of mitogenesis which might be responsible for the nonresponsiveness of the 3T3-TNR9 cells, we have examined in these cells the early protein phosphorylation events known to be associated with mitogenesis in the pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

1986
1986
1991
1991

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 25 publications
0
12
2
Order By: Relevance
“…3 had the appropriate position by mixing it with purified MAP kinase, which (as shown previously [37]) migrated at the same Mr as the pp42 spot (data not shown). We conclude that the TPA-induced tyrosine phosphorylation of pp42 is defective in the 3T3-TNR9 cell variant but that tyrosine phosphorylation of at least some 45-kDa proteins occurs in these cells, a result which explains the apparent discrepancy with our earlier report (7). However, as discussed in the legend to Fig.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…3 had the appropriate position by mixing it with purified MAP kinase, which (as shown previously [37]) migrated at the same Mr as the pp42 spot (data not shown). We conclude that the TPA-induced tyrosine phosphorylation of pp42 is defective in the 3T3-TNR9 cell variant but that tyrosine phosphorylation of at least some 45-kDa proteins occurs in these cells, a result which explains the apparent discrepancy with our earlier report (7). However, as discussed in the legend to Fig.…”
Section: Resultscontrasting
confidence: 57%
“…TNR9 cells possess normal levels of PK-C, and the activity and translocation of this enzyme in response to TPA appear to occur normally (7,18). A more recent report from Biemann and Erikson (5) indicates that the TPA-induced down-modulation of PK-C does not persist in TNR9 cells which are allowed to overgrow and form multilayers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…on May 11, 2018 by guest http://mcb.asm.org/ Downloaded from 3T3-TNR9 cells, in contrast to our earlier results (5). They also reported that 3T3-TNR9 cells, in contrast to parental 3T3 cells, were defective in the ability to down regulate PKC in response to chronic TPA treatment.…”
Section: Addendumcontrasting
confidence: 56%
“…This was surprising, since we generally find that TPA-induced phosphorylations are extremely rapid, requiring only a few minutes (5,6). Thus, the steady, prolonged increase in transporter phosphorylation in response to TPA may reflect not only the activation of protein kinase C but also the biosynthesis of new transporters or the translocation of transporters to a site where they are susceptible to phosphorylation by protein kinase C (22).…”
Section: Discussionmentioning
confidence: 96%